Valoración de servicios ecosistémicos y planificación: Una propuesta de gestión sostenible del turismo en humedales - Teba Félix-Massa (Atlantic Review of Economics (ARoEc), 2018)
– Despite the growing awareness that wetlands are extremely valuable ecosystems, they continue to degrade (Seo / Birdlife, 2018). Some authors (Pearce and Turner, 1995; De Groot et al., 2007; Barbier et al., 1997) agree about this is because they are not being managed in an optimal way because the full value of wetlands has not been taken into account, as well as the costs and benefits of their possible uses when economic development decisions have been taken in the planning carried out. This paper identifies and analyzes the different ecosystem services provided by wetlands, including tourism. In addition, a tourism management proposal is presented to limit negative impacts and to promote a balanced use of tourist and recreational activities in wetlands, as well as generate information that can contribute to understand both the economic benefits of wetland conservation and the economic impact and cost of degradation and destruction.
Keywords: Q01; Q26; Q51; Q57; O21; 330; Wetlands; ecosystem services; sustainable tourism; planning; economic valuation